2003
DOI: 10.1039/b306125f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of photochromism in salicylideneaniline: A femtosecond spectroscopic study

Abstract: Excited state intramolecular proton transfer (ESIPT) of salicylideneaniline enol and subsequent isomerization of the proton transferred keto structure to the final long-lived photochromic product has been studied in different solvents using femtosecond transient absorption and picosecond fluorescence spectroscopy. Three different types of transient absorption have been identified, viz. (a) from initially excited enol form, (b) proton transferred keto form and (c) corresponding to the final photochromic product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
122
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 29 publications
13
122
3
Order By: Relevance
“…It was also checked that no improvement can be obtained when including different number of components in the resolution. The profiles Ĉ and Ŝ extracted from MCR analysis are also found in quite good agreement with results obtained previously for this class of molecules in different solvents [7,31,32].…”
Section: Characterization Of the Photodynamics Of Sasupporting
confidence: 77%
See 2 more Smart Citations
“…It was also checked that no improvement can be obtained when including different number of components in the resolution. The profiles Ĉ and Ŝ extracted from MCR analysis are also found in quite good agreement with results obtained previously for this class of molecules in different solvents [7,31,32].…”
Section: Characterization Of the Photodynamics Of Sasupporting
confidence: 77%
“…The rate constant k 1 typically would describe an ultrafast transition ($ few femtoseconds) between the ground state and the excited state, which is usually not accessible from classical experimental data. The rate constants k 3 would correspond to the formation of a cis-keto intermediate ($200 fs) [7,32]. Finally, k 4 would correspond to the relaxation of this intermediate to the trans-keto photochromic form ($2 ps).…”
Section: Simulated Time-resolved Spectroscopic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism involves in the first step, an excited state intramolecular proton transfer (ESIPT) [15] which is of potential interest for fast optical switching applications and from fundamental point of view [16,17]. The generally accepted photoreaction is (1) an ESIPT between an enol form and a cis-keto form of the molecule and (2) a cis-trans isomerization to the trans-keto photoproduct [15,18,19]. Back reaction from the trans-keto state to the enol form can occur both by irradiation with visible light or by thermal conversion with a kinetics which ranges from a few ms in solution to several months in solid state (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important result with regards to applications where switching speed should be considered. Such hypothetical schemes for the photochromism of anils were made previously in several studies [27,28,31,42,43] but have never been shown directly, due to the presence of strong overlapping species with almost similar spectra.…”
Section: Discussionmentioning
confidence: 95%